A new ceramide from the leaves of Lannea schimperi (Hochst. ex A.Rich.) Engl. Issue 2 (17th January 2022) - Nguemo, Rolande Tsafack; Mbouangouere, Roukayatou; Bitchagno, Gabin Thierry M.; Tchuenguem, Roland; Temgoua, Elise Vanessa N.; Ndontsa, Blanche Laure; Mpetga, James Simo; Opatz, Till; Ngouela, Augustin Silvere; Tane, Pierre
Abstract: A new ceramide is being reported herein together with six known compounds from the methanol extract of the leaves of Lannea schimperi (Hochst. ex A.Rich.) Engl. The metabolites were obtained through repeated open column chromatography and were characterized by spectroscopic and spectrometric techniques. The radical-scavenging activity of the crude extract and isolated compounds was evaluated using the DPPH radical. The obtained results suggest the studied species as prominent candidate to fight reactive oxygen species (ROS). Abstract : UF0001